The impact of laparoscopic surgery in colorectal cancer resection with respect to the development of liver metastasis in the long-term - Rostirolla,Renata (2016)
ABSTRACT INTRODUCTION: Colorectal cancer (CRC) shows high incidence and mortality worldwide, particularly in Western and developed countries. The objective of this study is to evaluate the oncologic results during a minimum follow-up of 2 years of curable CRC patients submitted to laparoscopic resection in our environment, regarding to the development of hepatic metastases. METHODS: Medical records of 189 colon and rectal patients with potentially curable adenocarcinoma who have been submitted to laparoscopic resection have been reviewed through a retrospective cohort between January 2005 and March 2012 at a single institution regarded as reference to this type of treatment. Pearson's χ2 and Long-rank tests have been used for statistical analysis and data was analyzed by statistic package STATA version 11.0. RESULTS: The eligible population for the study was 146 patients, 91 women (62%), with a mean age of 61 ± 13 years. Minimum follow-up was 24 months, having an mean follow-up of 60 ± 27 months and an mean follow-up of global disease recurrence of 27 ± 11 months. Hepatic metastases occurred in 7.5% of the population, most from stage III, and the mean recurrence period was 25 ± 16 months. CONCLUSIONS: Laparoscopic resection for potentially curable CRC in this cohort did not change the long-term incidence of hepatic metastases, considering that our results are comparable to large randomized clinical trial results. Laparoscopic resection was effective and safe for analyzed patients, regarding long-term oncologic results.